Assessment the Relation between Breast Cancer and Blood Group - Sahar H. AI-Hindawi (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To assess the relation between breast cancer & blood groups, identify the importance of women age group and the relation of age with breast cancer. Methodology: The study was performed on (115) women who were diagnosed with breast cancer in different stages of disease and different ages. Blood samples were taken from them to demonstrate their blood groups and (20) fresh tumor tissue samples were obtained; the tumor tissue used as a source of lectin for hemagglutinate with erythrocyte of different blood groups. The study conducted at Baghdad Teaching Hospital and Radiation & Nuclear Medicine Hospital from January, 2007 through June 2007. Results: The study shows that the highest percentage of women having breast cancer were at age (40-59) years and women with (AB) blood group with significance differences from other blood groups. Recommendation: Early breast exanination for women with age group (40-59) years &with blood group (AB) for early detection for breast cancer, and early treatment.